2019
DOI: 10.1115/1.4043553
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microexplosion Phenomenon in Parent–Child Droplets of Water in Biodiesel Emulsions Enhanced by Different Surfactant Dosages and Hydrophilic–Lipophilic Balance Values

Abstract: This experimental study endeavors to investigate the evolution of microexplosion phenomenon of water in biodiesel emulsion droplets with the base fuel (B5) containing 95% diesel and 5% of palm oil methyl ester (POME). Parameters such as water content varied from 9%, 12%, and 15%, surfactant dosages of 5%, 10%, and 15% and the hydrophilic–lipophilic balance (HLB) values of 6, 7, 8, and 9 were varied to study its impact on microexplosion phenomenon. Three different sizes of emulsion droplets of approximately Ø2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Remarkably, the modification of HLB values in nanomaterials synthesis was implemented to boost the production of oil recovery and contact angle in water. 186 In the same year, Abdul Karim et al 187 observed and studied the micro-explosion occurrence of numerous size emulsion droplets through HLB values. The dosage of surfactants was mainly accountable on waiting time of this process.…”
Section: Factors Influencing Microbial Nanoparticle Synthesismentioning
confidence: 99%
“…Remarkably, the modification of HLB values in nanomaterials synthesis was implemented to boost the production of oil recovery and contact angle in water. 186 In the same year, Abdul Karim et al 187 observed and studied the micro-explosion occurrence of numerous size emulsion droplets through HLB values. The dosage of surfactants was mainly accountable on waiting time of this process.…”
Section: Factors Influencing Microbial Nanoparticle Synthesismentioning
confidence: 99%
“…Active research is currently focused on parent droplets of water-based solutions, slurries, and emulsions, including microand nano-emulsions [9][10][11][12]. It involves different heating arrangements with dominant convective, conductive, radiative, and mixed heat transfers [13][14][15][16] to determine the critical conditions sufficient for the parent droplet breakup and the limitations to the use of these effects in various engineering systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NO x reduction can be achieved either by absorption or as a result of lower combustion temperature. A normal water substitution to diesel emulsions ranges between 5% and 15% [14,15]. There is great enthusiasm for water-in-diesel emulsions due to the way that water, as micro-sized beads, results in favourable outcomes on fuel burning.…”
Section: Introductionmentioning
confidence: 99%
“…The above studies [16][17][18][19], as well as many others, focused on water in diesel emulsions and their emissions. The following studies presented water emulsification of binary fuels, B5 [14], B20 [15] and B40 [20]. In Reference [14], 5% palm oil methyl ester and 95% diesel were used with water content from 9-15% and surfactant dosages of 5-15%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation